2004
DOI: 10.1042/bj20030893
|View full text |Cite
|
Sign up to set email alerts
|

The role of the inhibitors of interleukin-6 signal transduction SHP2 and SOCS3 for desensitization of interleukin-6 signalling

Abstract: The immediate early response of cells treated with IL-6 (interleukin-6) is the activation of the signal transducer and activator of transcription (STAT)3. The Src homology domain 2 (SH2)-containing protein tyrosine phosphatase SHP2 and the feedback inhibitor SOCS3 (suppressor of cytokine signalling) are potent inhibitors of IL-6 signal transduction. Impaired function of SOCS3 or SHP2 leads to enhanced and prolonged IL-6 signalling. The inhibitory function of both proteins depends on their recruitment to the ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 46 publications
9
56
0
Order By: Relevance
“…A delay in the induction of IL-6 in the SCs was in contrast to the whole muscle and systemic response, which was more rapid (significant increases at 3 h in both mRNA and serum) and more robust compared with the young controls. This may be partially explained by the elevated basal SOCS3 in the muscle, which may have desensitized the SCs to IL-6 (20,62). The muscle stem cell niche is sensitive to age-related alterations in signaling molecules (15,23) and thus chronically elevated muscle IL-6 (as demonstrated at the mRNA level) may have negatively impacted the microenvironment of the SCs, impairing normal IL-6 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A delay in the induction of IL-6 in the SCs was in contrast to the whole muscle and systemic response, which was more rapid (significant increases at 3 h in both mRNA and serum) and more robust compared with the young controls. This may be partially explained by the elevated basal SOCS3 in the muscle, which may have desensitized the SCs to IL-6 (20,62). The muscle stem cell niche is sensitive to age-related alterations in signaling molecules (15,23) and thus chronically elevated muscle IL-6 (as demonstrated at the mRNA level) may have negatively impacted the microenvironment of the SCs, impairing normal IL-6 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, IL-6-mediated STAT3 activation is transient and continuous stimulation does not lead to permanent STAT3 activation (Fischer et al, 2003). Inactivation of IL-6-induced feedback inhibitors like SOCS1 and SOCS3 by hypermethylation might come into play.…”
Section: Discussionmentioning
confidence: 99%
“…7B); the time frame of these experiments is short, such that the LPS-mediated induction of CXCL9 and CXCL10 that occurs indirectly via autocrine IFN-␤ is not readily detectable. The IL-27 receptor is comprised of gp130 and WSX-1 subunits (13), and we and others have shown that gp130-mediated signaling is strongly inhibited by TLRs via a rapidly induced mechanism that is dependent on p38 and independent of de novo protein synthesis (45)(46)(47)(48)(49)(50)(51). Interestingly, inhibition of IL-27 signaling was induced rapidly, within 30 min of TLR stimulation (Fig.…”
Section: Activation Of Monocytes By Il-27 Is Abrogated By Tlrs Via a mentioning
confidence: 99%